2020
DOI: 10.1002/pits.22441
|View full text |Cite
|
Sign up to set email alerts
|

Can abacus course eradicate developmental dyscalculia

Abstract: Developmental dyscalculia (DD) is a specific mathematical learning disability, with a prevalence of around 3%-7% in the school-aged population. It negatively affects individuals, and even the national, development. Previous DD-intervention programs usually targeted on numerosity, number, simple arithmetic, or even general cognitive ability. The current study investigated the effect that a long-term (2-3 years) abacus course had on the prevalence of DD. Twelve classes of students were tested, half of which rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 81 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…Mathematical cognitive impairment is a complex phenomenon, covering two main areas: developmental calculation disorders and acquired calculation disorders. Developmental calculation disorders typically manifest during the natural developmental process of children, appearing as difficulties in number and calculation abilities without evident neural system damage or specific brain region developmental delays ( Lu et al, 2020 ). These difficulties extend beyond mathematical calculations, including number recognition, comparison, and estimation, possibly due to fundamental neurobiological defects such as working memory, attention, and executive function deficits ( Li et al, 2013 ; Bulthé et al, 2019 ; Klados et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical cognitive impairment is a complex phenomenon, covering two main areas: developmental calculation disorders and acquired calculation disorders. Developmental calculation disorders typically manifest during the natural developmental process of children, appearing as difficulties in number and calculation abilities without evident neural system damage or specific brain region developmental delays ( Lu et al, 2020 ). These difficulties extend beyond mathematical calculations, including number recognition, comparison, and estimation, possibly due to fundamental neurobiological defects such as working memory, attention, and executive function deficits ( Li et al, 2013 ; Bulthé et al, 2019 ; Klados et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research studies have revealed that early interventions show great potential for teaching at-risk dyscalculic pupils (Dowker, 2017;Butterworth, 2019). Researchers have proposed that pedagogical interventions can enhance dyscalculic pupils' mathematics learning, such as the Multisensory Teaching approach (Emerson & Babtie, 2014), the Concrete-Representational-Abstract approach (Bird, 2017), Intervention using an abacus (Lu et al, 2020), intensive intervention (Bryant et al, 2014), integer module intervention (Bryant et al, 2020), intervention combining many evidence-based practices (Powell et al, 2020), intervention based on best instructional practices (Van Garderen et al, 2020), and game-type intervention (Laski & Siegler, 2014). Other studies reported that dyscalculic pupils may gain substantial improvement through technology-based interventions such as computer-based intervention programs (Butterworth & Laurillard, 2010) and Augmented Reality (AR) technology (Miundy et al, 2017).…”
Section: Current Interventions For Teaching At-risk Dyscalculic Pupilsmentioning
confidence: 99%
“…It affects approximately 4 to 7% of school-aged children (Butterworth, 2019). Children with DD were found to show poor performance in symbolic (e.g., Arabic digits) and/or nonsymbolic (e.g., dots arrays) arithmetic (Butterworth, 2010; Lu et al, 2021; Price & Ansari, 2013). With a limited studies that have been conducted in this area, its underlying mechanisms remain controversial (De Smedt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%